Factors Predicting the Recurrence of Febrile Seizure in Siloam General Hospital: A Descriptive Analysis - Octavius, Gilbert S.; Handoko, Tan G. H.; Budiputri, Charista L.; Muljono, Michelle P.; Juliansen, Andry (Journal of Pediatric Epilepsy, 2021)
Febrile seizure (FS) is one of the most common pediatric neurologic disorders, affecting 2 to 5% of children between 6 months and 5 years. In 2008 to 2010, almost half of children with FS in Indonesia experienced recurrences. Various factors have been related to potential predictors for FS recurrence. However, available data reported inconsistent results. Considering its high recurrence rate, this study aimed to determine and assess the factors predicting the recurrence of FS. A cross-sectional study was done in Siloam General Hospital, Lippo Village. The study period was from December 2018 to December 2019, and data were obtained through medical records. Out of 60 participants, 41.7% had recurrent FS. No administration of rectal diazepam before admission (odds ratio [OR] = 6.42; 95% confidence interval [CI]: 1.20–34.2, p = 0.027) was a predictive factor of recurrent FS, while female sex (OR = 0.23; 95% CI: 0.64–0.80, p = 0.025) and shorter duration of the first FS (OR = 0.21; 95% CI 0.06–0.69, p = 0.008) were protective factors of recurrent FS. Identification of factors predicting the recurrence of FS is a powerful tool for clinicians. This study showed that no administration of rectal diazepam before admission was correlated with the risk of FS recurrence, while shorter duration of FS and female sex were protective factors of recurrent FS.
Keywords: simple febrile seizures; complex febrile seizure; recurrence; predictors; diazepam